IMPLEMENTASI PROGRAM “SABILULUNGAN” PEMBERDAYAAN MASYARAKAT RAKSA DESA DAlAM MENINGKATKAN PEMBANGUNAN FISIK DI DESA CILEUNYI KULON KECAMATAN CILEUNYI KABUPATEN BANDUNG PROVINSI JAWA BARAT - Abdurohim Abdurohim (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2018)
Sabilulungan Community Empowerment Program Village Raksa is a program of Bandung Regency Government is intended to improve the quality of physical infrastructure development through the active participation of government and community in the implementation of development in the village and utilize local resources independently. This program has been implemented by all villages in Bandung regency. Cileunyi Kulon Village is one of the targeted areas of Sabilulungan Community Empowerment Program of Raksa Desa especially in increasing the physical development in the area of the village. The purpose of this observation is to know how the implementation of Sabilulungan Village Community Empowerment Sabilulungan program, the factors that encourage and inhibit the implementation of the program, as well as government efforts in following up the inhibiting factors. The research method used is Descriptive research method with inductive approach. The data collection techniques used in the study are Observation, Interview, and Documentation. Implementation Sabilulungan Community Empowerment Program Village Raksa In Improving Physical Development In Cileunyi Kulon Village Cileunyi District Bandung Regency is one of government efforts in improving people’s welfare, especially in the field of physical prasaraana development. The results of observations that the authors do that the implementation of programs conducted by the village head cileunyi kulon is good enough, but still experiencing various obstacles. Inhibiting factors that occur include the problem: the budget is still minimal, and disbursements are divided into two stages resulting in inhibition of the program. The suggestion to be conveyed by the author in an effort to overcome these obstacles is increasing the budget to Sabilulungan Community Empowerment Program Village Raksa, facilitate the process of disbursement of funds and improve the performance of village officials. Keywords: impact, policy, development